Relevansi Investasi Tabungan Emas dalam Perspektif Fikih Klasik dan Fikih Kontemporer - Nadhriati, Melfi; Suparmin, Sudirman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
There are differences of opinion between previous (classical) and current (contemporary) scholars regarding the permissibility of storing gold. Because of these differences, in-depth study or research is needed regarding investing in gold savings, which in this case is focused on one of the financial institutions providing gold savings facilities, namely Bank Syariah Indonesia. This research aims to determine the perspective of classical and contemporary Fikih regarding the relevance of investing in gold savings, the cause of differences of opinion among them, and find the strongest perspective after the Munaqasyah Adillah was held. The research method that the author uses is a normative-empirical type of research with a comparative approach and legal sociology. From the study conducted by the author, the classical Fikih perspective says that it is not permissible to carry out gold buying and selling transactions non-cash or delayed because the illat between gold and money is the same, namely tsamaniyah (price/means of payment). Meanwhile, according to contemporary jurisprudence, carrying out non-cash or deferred gold buying and selling transactions is permitted, provided that the gold is not a legal medium of exchange at that time but is in the form of goods (sil'ah). Even though some opinions allow non-cash gold buying and selling transactions, we should stick to the opinion of Salaf scholars.